Prey diversity for Three Species Herons in Pulau Dua Nature Reserve Serang Distrik, Banten Province - DEWI ELFIDASARI (Society for Indonesian Biodiversity, 2006)
The diversity of prey consumed by three species herons (Casmerodius albus, Egretta garzetta and Bubulcus ibis) was studied in Pulau Dua Nature Reserve Serang, Banten Province using video tapes by following a focal individual for five minutes. In the laboratory the film was analysed every minutes to select complete sequences of feeding behavior in foraging site. There were differences on diversity and size of prey that consumed by three species herons among the different feeding locations. Casmerodius albus which was feeding on mudflat and fisheries consumed Chanos chanos (15.6%), Oreochromis sp (9.4%) and Periophtalmus sp. (7.3%), and 36.5% couldnâ€™t be identified. Egretta garzetta was feeding on mudflat, fisheries and rice-field, consumed Periophtalmus sp (15.4%), Mugil dussumeieri (7.9%), Chanos chanos (4.7%), Oreochromis sp (0.5%), including small frog and crustacean (0.5%). Bubulcus ibis was feeding on rice-field and grassland, consumed many variety of insects (92 %) and many variety of snail (1.9%) in their diet. The insects that B. ibis consumed including grasshopper (26.8%), caterpillar (0.9%) and other invertebrates (worm, crustacean) that could not be identified (64.3%).Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Prey, diversity, herons, Pulau Dua.